Serotype diversity of Streptococcus pneumoniae in children with chronic bronchopulmonary pathology in the pre-vaccination and post-vaccination periods - T. M. Komyagina; A. S. Tryapochkina; N. M. Alyabieva; A. V. Lazareva; A. P. Fisenko (Association of Paediatric Allergists and Immunologists of Russia (APAIR), 2024)
.